Community-Based Global Health Program for Maltreated Children and Adolescents in Brazil: The Equilibrium Program - Marques, Andrea Horvath; Oliveira, Paula Approbato; Scomparini, Luciana Burim; Silva, Uiara Maria Rêgo e; Silva, Angelica Cristine; Doretto, Victoria; Medeiros Filho, Mauro Victor de; Scivoletto, Sandra (Frontiers in Psychiatry, 2015)
The maltreatment of children and adolescents is a global public health problem that affects high and low-middle income countries (“LMICs”). In the United States, around 1.2 million children suffer from abuse, while in LMICs such as Brazil these rates are much higher (an estimated 28 million children). Exposition to early environmental stress has been associated with suboptimal physical and brain development, persistent cognitive impairment and behavioral problems. Studies have reported that children exposed to maltreatment are at high risk of behavioral problems, learning disabilities, communication and psychiatric disorders and general clinical conditions such as obesity and systemic inflammation later in life. The aim of this paper is to describe The Equilibrium Program (“TEP”), a community-based global health program implemented in São Paulo, Brazil to serve traumatized and neglected children and adolescents. We will describe and discuss TEP’s implementation, highlighting its innovation aspects, research projects developed within the program as well as its population profile. Finally, we will discuss TEP’s social impact, challenges and limitations. The program’s goal is to promote the social and family reintegration of maltreated children and adolescents through an interdisciplinary intervention program that provides multi-dimensional bio-psycho-social treatment integrated with the diverse services needed to meet the unique demands of this population. The program’s cost-effectiveness is being evaluated to support the development of more effective treatments and to expand similar programs in other areas of Brazil. Policy makers should encourage early evidence-based interventions for disadvantaged children to promote healthier psychosocial environments and provide them opportunities to become healthy and productive adults. This approach has already shown itself to be a cost-effective strategy to prevent disease and promote health.